Minimum wage as one of the main state social guarantees - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Тарасенко, Вікторія Сергіївна; Тарасенко, В. С.; Тарасенко, Виктория Сергеевна; Tarasenko, Viktoriia S.; Волошина, Світлана Михайлівна; Волошина, С. М.; Волошина, Светлана Михайловна; Voloshyna, Svitlana M.; et al. (Periodicojs Academic Publisher, 2020)
The definition, goals of the minimum wage, the criteria for its determination, the sphere of application of the system of setting the minimum wage, the procedure for its establishment, as well as regulation and implementation were analyzed in the article. Comparative legal analysis was carried out of the acts of national labor legislation for compliance with international and European standards, enshrined in conventions and recommendations of the International Labor Organization , Attention is drawn to the fact that Ukraine has not yet undertaken obligations under paragraph 1 of Art. 4 of the European Social Charter (revised).The essence and significance of the minimum wage as one of the main state social guarantees is revealed, taking into account changes and amendments, made by the Legislation of Ukraine. The ratio of the category "minimum wage" and the category "subsistence level set for able-bodied persons on January 1 of the calendar year" is determined.

У статті проаналізовано визначення, цілі мінімальної заробітної плати, критерії її визначення, сфера застосування системи встановлення мінімальної заробітної плати, порядок її встановлення, а також регулювання та впровадження. Проведено порівняльно-правовий аналіз актів національного законодавства про працю на відповідність міжнародним та європейським стандартам, закріпленим у конвенціях та рекомендаціях Міжнародної організації праці. Звертається увага на те, що Україна досі не взяла на себе зобов’язання за п. 1 ст. 4 Європейської соціальної хартії (переглянута). Розкрито сутність і значення мінімальної заробітної плати як однієї з основних державних соціальних гарантій з урахуванням змін та доповнень, внесених законодавством України. Визначається співвідношення категорії «мінімальна заробітна плата» та категорії «прожитковий мінімум, встановлений для працездатних осіб на 1 січня календарного року».
Kivalov S. Minimum wage as one of the main state social guarantees / S. Kivalov, V. Tarasenko, S. Voloshyna, R. Chanyshev, O. Shchukin // Revista Gênero E Interdisciplinaridade. - Vol. 1. - No. 01. - Periodicojs Academic Publisher, 2020. https://doi.org/10.51249/gei.v1i01.43
Keywords: wages; minimum wages; state social guarantees; international standards; legislation of Ukraine; заробітна плата; мінімальна заробітна плата; державні соціальні гарантії; міжнародні стандарти; законодавство України; Research Subject Categories::LAW/JURISPRUDENCE